Selective binding of benzoquinone with a Pt-II-cyclophane constructed on the skeleton of N,N `-bis(salicylidene)-p-phenylenediamine: synthesis and spectroscopic studies - Kumari, Niraj; Prajapati, Rishikesh; Dixit, Mudit; Mishra, Lallan (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2009)
The Schiff base NN'-bis(salicylidene)-p-phenylenediamine has been complexed with Pt(en)Cl-2 and the resulting Pt-II-cyclophane, [Pt(en)L](2)center dot 4PF(6), reacted with phenol, resorcinol, hydroquinone or benzoquinone in DMSO solution. Their binding has been monitored by the variation in the corresponding UV-visible and emission spectral patterns. The binding properties are compared with the earlier reported Zn-II-cyclophane [Zn(bpy)L](2) (bpy = 2,2'-bipyridine). A few solid adducts of phenol and benzoquinone with the Pt-II-cyclophane complex and hydroquinone as well as that of resorcinol with the Zn-cyclophane have also been synthesized and characterized.
Keywords: Coordination chemistry; Cyclophanes; Metallocyclophanes; platinum; Schiff bases

Metal [Zn(II), Cd(II)], 1,10-phenanthroline containing coordination polymers constructed on the skeleton of polycarboxylates: synthesis, characterization, microstructural, and CO2 gas adsorption studies - Yadav, Pramod Kumar; Kumari, Niraj; Pachfule, Pradip; Banerjee, Rahul; Mishra, Lallan (Crystal Growth & Design, 2012)
{Four new coordination polymers have been obtained by the reaction of metal [Zn(II), Cd(II)], 1,10-phenanthroline separately with two carboxylic acids, [biphenyl-4,4'-dicarboxylic acid (4,4'-H(2)BDA),and 4,4'-azodibenzoic acid (4,4'-H(2)ADA)]. The crystal structures of the resulting complexes of type {[Zn(4,4'-BDA)(Phen)(2)center dot HCON(CH3)(2)}(n) (1), {[Cd(4,4'-BDA)(Phen)](2)center dot H2O\